2008
DOI: 10.1016/j.jcorpfin.2008.02.004
|View full text |Cite
|
Sign up to set email alerts
|

How do firms adjust director compensation?

Abstract: This paper examines outside director compensation for a sample of 237 Fortune 500 firms over the 1998-2004 period. We document a trend towards fixed-value equity compensation and away from cash only and fixed-number equity compensation. Adjustments to director compensation are consistent with firms targeting a market level of compensation, and firms that deviate from their market wage symmetrically adjust compensation back toward the market level. We also document the relation between changes in compensation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
60
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(63 citation statements)
references
References 29 publications
(43 reference statements)
0
60
0
3
Order By: Relevance
“…Individuals seek to maintain an equilibrium between the inputs that they bring to a job and the outcomes they receive from it. Farrell et al (2008) found that, contrary to the process for executive remuneration, INEDs' remuneration is set for a group of individuals as a whole, i.e.…”
Section: Hypotheses' Developmentmentioning
confidence: 97%
See 2 more Smart Citations
“…Individuals seek to maintain an equilibrium between the inputs that they bring to a job and the outcomes they receive from it. Farrell et al (2008) found that, contrary to the process for executive remuneration, INEDs' remuneration is set for a group of individuals as a whole, i.e.…”
Section: Hypotheses' Developmentmentioning
confidence: 97%
“…Among the few empirical studies which are not descriptive, most rely on an economic approach based on an optimal contracting perspective of agency theory in a single institutional setting 1 . Those studies have mainly focused on the adoption of performance-based remuneration to reduce the potentially misaligned interest between shareholders and INEDs (e.g., Hempel and Fay, 1994;Boyd, 1996;Bryan, Hwang, Klein & Lilien , 2000;Cordeiro et al, 2000) or the adoption of meeting fees to provide INEDs with an incentive to exert more effort (Hempel and Fay 1994;Bryan et al 2000;Brick, Palmon & Waldet, 2006;Farrell, Friesen & Hersch, 2008;Adams and Ferreira 2008). A more comprehensive agency theory framework was adopted by Cordeiro et al (2000), Andreas et al (2012) and Marchetti & Stefanelli (2009).…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…We base our research on the companies listed in the German Prime Standard (market segment with the highest disclosure and reporting standards for German listed companies) during the years 2005 until 2009 and rely on a matched sample for our analyses (Arthaud-Day et al 2006;Cannella et al 1995;Kulich et al 2011). We exclude financial companies from the sample-identified by an SIC code between 6,000 and 6,799 (Farrell et al 2008)-because their firm characteristics such as leverage and total assets (important control variables for our matching and regressions) differ from those of non-financial companies and would thus lead to estimation biases. The final database consists of an unbalanced panel of 1,458 firm years.…”
Section: Sample Definitionmentioning
confidence: 99%
“…3 We choose 2004 since it is post Sarbanes Oxley and is also the last year that IRRC collects director data. 4 For details, see Farrell et al (2008). 5 The midpoint is used so that if we have two pairs, say ($100 000, $50 000) and ($50 000, $100 000), we get the same percentage difference.…”
Section: Sample Selection and Pairwise Analysismentioning
confidence: 99%